THE PARAMETERS ANALYSIS OF ALKALINE AND ACID MEANS EFFECTIVE USING FOR DAIRY INDUSTRY EQUIPMENT - Onyshchenko, V. O.; Filonych, O. M.; Storozhenko, D. O.; Senenko, N. B.; Bunyakina, N. V.; Horobets, D. O.; Kysil, V. R. (Scientific Progress & Innovations, 2019)
The results of the parameters analysis of the alkaline and acid means efficient using for cleaning and disinfecting dairy industry equipment in one washing cycle Clean-In-Place (CIP) mode are presented. These solutions were created, protected by Ukrainian patents and suggested for using by the authors. In the previous studies, the absolute individual washing capacities of both solutions were proven. The optimization of the alkaline and acidic means using conditions was carried out at minimal temperatures recommended by the standard. Maximal possible dilution degrees of washing properties were determined. Dairy equipment washing in the industry according to the standard of Ukraine, as well as the results of researches and recommendations of Ukrainian and foreign scientists, requires using both solutions in one washing cycle. That is why, in order to identify the best effect, the optimization of the conditions for their using was carried out. In the work, the results of experimental studies of the alkaline and acid solutions washing capacity for washing dairy industry equipment internal surfaces in the СIP mode under different degrees of dilution and minimal temperatures are presented. The advantages of the developed and suggested means, as well as high effectiveness of their complex application, are shown. The optimal conditions for conducting high-quality washing are defined and suggested. The satisfactory washing effect of milk contaminants in the static mode using alkaline and acid detergents, created by the authors, at 1:9 diluting and maximal permissible temperature regimes was proved. The results of removing 3-day milk contaminations when the temperature regime of acid treatment is decreased to t=65°C at 1:9 dilution of both solutions are presented. The effectiveness of detergents to remove one-day milk film with decreasing the temperature of acid treatment to t=60°C at 1:9 dilution of both solutions is shown. The optimal conditions for the complex application of alkaline and acid detergents while washing the dairy industry equipment in CIP-mode created by the authors are detected. High washing effectiveness under these conditions is proven. Since the obtained results create a good prognosis for satisfactory disinfection effect, in future there is the necessity to determine the effectiveness of removing microorganisms with the suggested means and optimize the conditions for their using.